Adaptive Control of Space Robot Despinning Tumbling Target Using Flexible Brushes - Shengxin Sun; Cheng Wei; Zhuoran Huang; Hao Wu; Haibo Zhang; Jianchun Lu; Yan Du (International Journal of Aerospace Engineering)
A flexible brush mechanism is designed and mounted at the end of a seven-degree-of-freedom robotic arm to despin a tumbling target. The dynamics model of the flexible brush is established using the absolute nodal coordinate method (ANCF), and its contact collision with the solar wing of the tumbling target is analysed. The H∞ optimal control is proposed for a seven-degree-of-freedom robotic arm during despinning of a tumbling target while ensuring the global robustness and stability. Simulations verify that the despinning strategy can successfully eliminate the rotation speed and is feasible and effective.